2017
DOI: 10.1021/acs.energyfuels.7b02305
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Synthesis of Nitrogen- and Sulfur-Enriched Hierarchical Porous Carbon for High-Performance Supercapacitor

Abstract: In this work, we present a simple and facile method for the nitrogen (N)- and sulfur (S)- doped porous three-dimensional (3D) spongelike carbon materials via direct pyrolysis of N and S containing polymer N,N′-methylene-bis-acrylamide cross-linked poly­(acrylamide-co-2-acrylamido-2-methyl-1-propanesulfonic acid) at varying temperatures under inert atmosphere. The obtained nitrogen- and sulfur-doped porous carbons (NSPCs) possess 3D hierarchical porous structure and contain a significantly high amount of N and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 46 publications
0
24
0
Order By: Relevance
“…3f. Overall, the [33,47,48]. The incorporated sulfur species into the carbon framework could influence the surface charge and offer up pseudocapacitive effect [49].…”
Section: Structural Characterizationmentioning
confidence: 99%
“…3f. Overall, the [33,47,48]. The incorporated sulfur species into the carbon framework could influence the surface charge and offer up pseudocapacitive effect [49].…”
Section: Structural Characterizationmentioning
confidence: 99%
“…Few groups sparked enthusiasm in the direct synthesis of hierarchically porous carbon materials with prominent activity derived from heteroatom doping, such as hydrothermal reaction, [ 21,22 ] carbonization of polymer, [ 23,24 ] and chemical modification. [ 25,26 ] Mehare et al [ 27 ] reported the N‐ and S‐codoped porous 3D sponge‐like carbon materials via synthesizing the poly(acrylamide‐ co ‐2‐acrylamido‐2‐methyl‐1‐propanesulfonic acid‐ co ‐ N , N ′‐methylene‐ bis ‐acrylamide) (poly(AM‐ co ‐AMPS‐ co ‐MBAM)) (acrylamide (AM), cross‐linked (co), 2‐acrylamido‐2‐methyl‐1‐propanesulfonic acid (AMPS), N,N′‐methylene‐bis‐acrylamide (MBAM)) and the subsequent carbonization. It exhibits high mass capacitance (230 F g −1 at 1 A g −1 ) and >10 000 cycle stability at 10 A g −1 , which is attributed to high N and S contents with hierarchical porous structures.…”
Section: Introductionmentioning
confidence: 99%
“…The semicircular radius of PC‐10‐10 in the high‐frequency region is smaller than that of Blank‐C. It indicates that the charge transfer resistance of the electrode material is smaller, [ 63 ] primarily due to the effective change of wettability after P/O‐doping. The specific capacitance/rate performance also shows the same trend, and compared with the reported redox additive for SCs, PC‐10‐10 provides higher energy density even at high discharge rate (Figure 6d).…”
Section: Resultsmentioning
confidence: 99%